Scaling analysis of solving algorithms for canonical problem of dispatching in the context of dynamic programming - Fedosenko, Yuriy S.; Reznikov, Mikhail B.; Plekhov, Aleksandr S.; Chakirov, Roustiam; Houlden, Nigel (2017 Internet Technologies and Applications (ITA), 2017)
The paper analyses computational model based on dynamic programming for platforms with multicore processors and heterogeneous architectures with FPGA. The models are applied for solving a canonical problem of dispatching where the computation time significantly depends on the problem scale factor. The parallel algorithms of NP-hard problem of dispatching are complicate and require intensive RAM data exchange. In order to reduce the computation time, it is suggested to use FPGA as a coprocessor providing massively parallel computation and increase the operational performance of the system in one order.